The role of symbolism in the philosophy of Nishida Kitarõ - Crespín Perales, Monserrat (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
As an alternative to the multiple studies about the philosophy of Nishida Kitarõ (1870- 1945), this essay wants to present a research line about questions not normally considered in the interpretation of his philosophy. The intention is to demonstrate how a close look to the idea of «symbol» and the citations of symbolist poetry in Nishida’s works can offer a plausible key for a better comprehension of his selfconsciousness system that appears in works as Intuition and Reflection in Self-consciousness (1917) or Problems of consciousness (1920).